2019
DOI: 10.3390/nu11030700
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of CISD2 and Influence of Curcumin on CISD2 Expression in Aged Animals and Inflammatory Cell Model

Abstract: Background: Inflammation and mitochondrial dysfunction have been linked to trauma, neurodegeneration, and aging. Impairment of CISD2 expression may trigger the aforementioned pathological conditions in neural cells. We previously reported that curcumin attenuates the downregulation of CISD2 in animal models of spinal cord injury and lipopolysaccharide (LPS)-treated neuronal cells. In this study, we investigate (1) the role of CISD2 and (2) how curcumin regulates CISD2 in the aging process. Materials and method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 49 publications
0
39
0
Order By: Relevance
“…LPS-stimulated ALT cells were used as an in vitro model of cellular injuries. This model recapitulates SCI-associated aberrant astrocyte activation and inflammation [ 25 , 26 , 30 ]. The cells were treated with 20 μ g/mL LPS for 24 h and subjected to qRT-PCR and western blotting.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…LPS-stimulated ALT cells were used as an in vitro model of cellular injuries. This model recapitulates SCI-associated aberrant astrocyte activation and inflammation [ 25 , 26 , 30 ]. The cells were treated with 20 μ g/mL LPS for 24 h and subjected to qRT-PCR and western blotting.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to mitochondrial dysfunction, CISD2 mitigates CNS injury-induced inflammatory response. Aging, neurodegeneration, and trauma are associated with downregulated CISD2 expression, which enhances the inflammatory response and exacerbates mitochondrial dysfunction [ 25 , 26 ]. Therefore, therapeutic targeting of CISD2 can aid in preventing the exacerbation of inflammation and mitochondrial dysfunction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…High inflammation due to microglial activation has been demonstrated underlying the pathogenesis of various neurodegenerative diseases in the CNS and neurodegenerative dementia (Thomas et al, 2015;Raz et al, 2016). In our previous study, we demonstrated that the attenuated CISD2 expression is associated with the aging process and leads to the inflammatory response (Lin et al, 2015(Lin et al, , 2019. Hence, we sought to determine whether CISD2 deficiency in microglia results in the inflammatory cascade as well as the likelihood that these detrimental insults influence microglia polarization.…”
Section: Knockdown Of Cisd2 Expression Augmented Inflammatory Signalimentioning
confidence: 98%